1992
DOI: 10.1016/0014-5793(92)80715-s
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of oligomeric organization of antenna bacteriochlorophyll c in green bacterium Chloroflexus aurantiacus by spectral hole burning

Abstract: Spectral hole burning has been used to prove cxpcrimcnially the cxislcnce in natural antenna of one of the predicted structural optimizing factors -antenna pigment oligomcrization [J, Theor. Biol. I40 (1989) lG7]-ensuring high cllicicncy ofexcitation energy transfer from antenna toreaction center, This point has been examined for ~hc chlorosomal antenna of green bacterium Cllkurqf/~srrs aurunfiucus by hole burning in fluorescence excitation and emission spectra of intact cells at I .X K. The prrsistcnt hole s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 11 publications
4
49
1
Order By: Relevance
“…We observed that the CD intensity of low-light chlorosomes only doubled upon treatment with proteinase K compared to a fivefold increase in the high-light chlorosomes. There is some evidence that BChl c in the chlorosome is organized as oligomers [8,9], which may be bound to protein in order to maintain parallel transition moments between clusters of BChl c [2.5,26]. There are several reports that BChl c aggregates in hexane [27,28], in aqueous suspension, or after LDS treatment [4], and after proteolytic treatment [4,18] exhibited higher rotational strength than BChl c in chlorosomes of ChlorojZexus auruntiucus.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the CD intensity of low-light chlorosomes only doubled upon treatment with proteinase K compared to a fivefold increase in the high-light chlorosomes. There is some evidence that BChl c in the chlorosome is organized as oligomers [8,9], which may be bound to protein in order to maintain parallel transition moments between clusters of BChl c [2.5,26]. There are several reports that BChl c aggregates in hexane [27,28], in aqueous suspension, or after LDS treatment [4], and after proteolytic treatment [4,18] exhibited higher rotational strength than BChl c in chlorosomes of ChlorojZexus auruntiucus.…”
Section: Discussionmentioning
confidence: 99%
“…Using the standard approach to the exciton-phonon problem in molecular crystals, we discovered that none of the earlier proposed models of BChl aggregation in chlorosomal antennae displays the in vivo exciton level structure of a BChl aggregate revealed by hole burning experiments on intact cells of different green bacteria [7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, experimental hole burning spectra of chlorosomal antennae of green bacteria show a broad absorption spectrum due to many electronic (exciton) levels. The higher levels have ,-~ 98% of the total oscillator strength [7][8][9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the structural optlmizlng factors is oligomerization of antenna pigments [2). The chlorosome of green bacteria contalning several thousands of antenna bacteriochlorophyll (BChl) c,d or e molecules in an aggregated state is the most convincing example of natural antenna of oligomeric type (3)(4)(5). The discovered strong orientational ordering of the near-infrared transition dipoles of BChl c in situ (6) suggested that an elementary BChl aggregate has the form of a linear chain.…”
Section: Introductionmentioning
confidence: 99%